Modernization and revolution in China - Grasso, June M., 1951-; Corrin, Jay P., 1943-; Kort, Michael, 1944- (New York ; London : Routledge Taylor & Francis Group, 2018)
"Extensively revised and fully updated in this fifth edition, this popular textbook conveys the drama of China's struggle to modernize against the backdrop of a proud and difficult history. It features new analysis of the issues facing China's fifth generation of leaders, including the current economic climate, China's relations with its neighbours and the United States, the latest Tibetan crisis, and the election of Xi Jinping. Incorporating new analytical summaries in each chapter and updated suggested readings, this new edition covers: - The breakdown of imperial China in the face of Japanese and Western encroachments - The early struggles between the ideologies and armies of Chiang Kai-shek and Mao Zedong - China's bitter and costly war with Japan - The final shootout that sent Chiang to Taiwan and Mao to Beijing - The turbulent first decades of the People's Republic - The triumphant hosting of the 2008 summer Olympics and the dramatic shift to a globalizing economic strategy. Spanning the years from China's defeat in the Opium Wars to its current status as a potential superpower, the fifth edition of Modernization and Revolution in China is essential reading for courses on Modern Chinese History, Chinese Politics and Modern East Asia"--
The Middle Kingdom -- Patterns of traditional Chinese life -- Imperial breakdown and Western invasion -- The new Chinese Republic -- Nationalists and communists -- China at war -- Creating the new order 1949-1957 -- The great leap and the bad fall -- The cultural revolution -- A second revolution: the reforms of Deng Xiaoping -- The era of Jiang Zemin -- The fourth generation -- The era of Xi Jinping: the fifth generation of Chinese leadership.
Includes bibliographical references and index.
Keywords: China -- History -- 19th century; China -- History -- 20th century